Efektivitas Pola Komunikasi Guru Dan Siswa Tunarungu Di Slb Negeri 1 Karawang Barat - Sari, Nabila Novinka; Nursanti, Siti; Santoso, Made Panji Teguh (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by deaf students, each of whom has different deficiencies and communication abilities in the teaching and learning process. Interpersonal communication patterns have an important role in the teaching and learning process to help teachers and deaf students to communicate during learning. Interpersonal communication patterns are applied so that the teaching and learning process can run effectively and learning objectives are achieved. This research uses a qualitative method with a descriptive approach. The aim of this research is to find out the obstacles and solutions to interpersonal communication patterns between teachers and deaf students in the teaching and learning process at SLB Negeri 1 West Krawang. The theory used in this research is the SOR (Stimulus, Organism, Response) theory by Hovland in 1953. The results of the research show that teachers' interpersonal communication patterns with deaf students in the teaching and learning process occur in one direction (linear), two directions (interactive), in many directions (transactional) with the help of learning methods, namely lecture, question and answer and media methods. The six informants agreed that the application of interpersonal communication methods and patterns can help the communication process during teaching and learning to be effective and in line with expectations. The obstacle is that deaf students have minimal knowledge of vocabulary and master different languages ​​for each child, and to overcome this is by using media methods such as pictures, videos, writing, and so on.